2015
DOI: 10.1002/hed.23992
|View full text |Cite|
|
Sign up to set email alerts
|

Glottic cancer in patients without complaints of hoarseness

Abstract: Patients with glottic cancer without complaints of hoarseness were diagnosed at an earlier stage than those with hoarseness. Accumulation of more cases may lead to better survival of patients with glottic cancer without hoarseness compared to those with hoarseness. Checking the larynx of patients without hoarseness or encouraging internists to check the larynx when performing gastroscopic or respiratory examinations may lead to improvement of glottic cancer prognosis. © 2015 Wiley Periodicals, Inc. Head Neck 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In contrast to supraglottic carcinoma, which frequently presents with cervical lymph node involvement from early T stages 12 and the reported neck metastasis rate ranges from 20% to 33%, 13,14 the paucity of lymphatic drainage in the glottis region results in low rates of cervical involvement, with 0.4%-6.5% GSCC cases initially presenting with neck metastases from the literature. 12,13,15,16 In our research, 67 (5.1%) of 1319 patients [15 (1.6%) from the 925 patients who had T1-T2 diseases and the other 52 (13.2%) from the 394 patients who had T3-T4 diseases) had pathologically confirmed LNM. Meanwhile, 17 patients (5 from patients with T1-T2 stages and 12 from patients with T3-T4 stages) were diagnosed with LNM by imaging and pathological examination during the post-operative follow-up within 6 months from initial surgery and were identified as having occult neck involvement at the time of initial treatment and categorized as the LNM group.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast to supraglottic carcinoma, which frequently presents with cervical lymph node involvement from early T stages 12 and the reported neck metastasis rate ranges from 20% to 33%, 13,14 the paucity of lymphatic drainage in the glottis region results in low rates of cervical involvement, with 0.4%-6.5% GSCC cases initially presenting with neck metastases from the literature. 12,13,15,16 In our research, 67 (5.1%) of 1319 patients [15 (1.6%) from the 925 patients who had T1-T2 diseases and the other 52 (13.2%) from the 394 patients who had T3-T4 diseases) had pathologically confirmed LNM. Meanwhile, 17 patients (5 from patients with T1-T2 stages and 12 from patients with T3-T4 stages) were diagnosed with LNM by imaging and pathological examination during the post-operative follow-up within 6 months from initial surgery and were identified as having occult neck involvement at the time of initial treatment and categorized as the LNM group.…”
Section: Discussionmentioning
confidence: 53%
“…GSCC ranks first among the three types of carcinoma in the laryngeal region. In contrast to supraglottic carcinoma, which frequently presents with cervical lymph node involvement from early T stages 12 and the reported neck metastasis rate ranges from 20% to 33%, 13,14 the paucity of lymphatic drainage in the glottis region results in low rates of cervical involvement, with 0.4%–6.5% GSCC cases initially presenting with neck metastases from the literature 12,13,15,16 . In our research, 67 (5.1%) of 1319 patients [15 (1.6%) from the 925 patients who had T1‐T2 diseases and the other 52 (13.2%) from the 394 patients who had T3‐T4 diseases) had pathologically confirmed LNM.…”
Section: Discussionmentioning
confidence: 67%
“…Approximately 60% of the estimated 13,560 new cases of larynx cancer in 2015 had their anatomic origin in the glottis . Due to the hoarseness that often accompanies even small lesions in the glottis, these cases typically present in an early stage . This is encouraging given the relatively good prognosis for such cases (90% 5‐year relative survival rate for stage I, 74% for stage II)…”
Section: Introductionmentioning
confidence: 86%
“…Smok-ing is a well-known risk factor for the development of malignancies in the head and neck region [18]. A Japanese study reported that the incidence of smoking was higher among patients with glottic cancer without dysphonia than among patients with voice complaints [19]. Smokers have chronic voice changes related to vocal edema or reflux laryngitis.…”
Section: Discussionmentioning
confidence: 99%
“…Tachibana et al reported that glottic cancer patients without hoarseness had a better disease-specific survival than those with hoarseness [19]. They claimed that glottic cancer patients without complaints of hoarseness were diagnosed at earlier stages.…”
Section: Discussionmentioning
confidence: 99%